Design and analysis of an aircraft composite hinge bracket using finite element approach - Wai, Chee Mun; Rivai, Ahmad; Bapokutty, Omar (Trans Tech Publications, 2014)
The use of composite materials in aircraft structures have been increasing for the past decade. The anisotropic and heterogeneous nature of composites remains a major challenge to the design and analysis of composite aircraft structures. Composite structures require a different design approach compared to the design of metallic structures. This paper aims to provide a step by step definitive guide to design and analyze composite structures using finite element approach. A simplified design model for the composite structural design was used to analyze an aircraft composite hinge bracket. The composite hinge bracket which is made of IM7/8552 laminated composite plates was successfully designed with a margin of safety of 0.216 and a weight savings of 43.77 percent was estimated.